ПІДГОТОВКА ВИХОВАТЕЛІВ ДО РИТМІЧНОЇ ОРГАНІЗАЦІЇ НАВЧАЛЬНО-ВИХОВНОГО ПРОЦЕСУ - Litvin, L. (Continuing Professional Education: Theory and Practice, 2019)
The methodological principles of the waldorf kindergarten teachers` preparation to the rhythmic organization of the educational process are defi ned in the article; the weekly rhythm of the children`s group is observed in the article; the signifi cance of the day`s, week`s, month`s and year`s rhythms for the promotion of the children`s health and forming their high ability to adapt to the life changes is emphasized in the article